2010
DOI: 10.1007/s10464-010-9298-9
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Improving After‐School Programs to Enhance Youth’s Personal Growth and Adjustment: A Special Issue of AJCP

Abstract: Participating in after-school programs (ASPs) has become a common experience for children. This special issue provides a perspective on the current status of research on ASPs. This introductory article overviews the historical and current context of ASPs and then describes a developmental ecological model to guide research in this area. The model offers a framework from which to organize and synthesize the research presented in this issue. Key principles include a holistic view of development that recognizes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 36 publications
1
46
0
8
Order By: Relevance
“…To illustrate, extensive empirical data suggest that afterschool programs can play a critical role in children's psychosocial development, especially for children living in communities of concentrated urban poverty (Durlak, Mahoney, Bohnert, & Parente, 2010). Despite their potential, however, program impact is often compromised by the extensive mental health needs of children and the pervasive poverty in which they live.…”
Section: Universalmentioning
confidence: 99%
“…To illustrate, extensive empirical data suggest that afterschool programs can play a critical role in children's psychosocial development, especially for children living in communities of concentrated urban poverty (Durlak, Mahoney, Bohnert, & Parente, 2010). Despite their potential, however, program impact is often compromised by the extensive mental health needs of children and the pervasive poverty in which they live.…”
Section: Universalmentioning
confidence: 99%
“…In other words, supportive contexts (such as after-school programs) that match a child's characteristics will enhance development. More specifically, researchers have suggested that developmental contexts which provide children with strong role models, encourage positive peer relationships, and support self-esteem may facilitate children's feelings of control over their environment and their emotional self-regulatory abilities (e.g., Chorpita & Barlow, 1998;Crick & Dodge, 1994;Durlak, Mahoney, Bohnert & Parente, 2010;Grossman, Campbell & Raley, 2007). Children who take advantage of after-school programs are able to participate in academic and extracurricular activities that enhance not only their academic skills, but also their social, behavioral, and physical skills, whereas their unsupervised counterparts spend much of their time watching television (Posner & Vandell, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Different from alternative preventive procedures (e.g., aggressive behavior reduction programs, remedial education) that focus on students' deficits, after-school activities provide a bridge towards more conventional social relationships and behavior by capitalizing on individual interests, achievements, and motivation for schooling (e.g., Czikszentmihayli, 1990;Durlak, Mahoney, & Bohnert, 2010;Larson, 2000). On this score, several studies have found that after-school activity involvement is linked to peer relationship formation and positive peer status.…”
Section: Protective Aspects Of Extracurricular Activitiesmentioning
confidence: 99%